USING MULTILINGUALISM TO ADVANTAGE IN ENGLISH DEPARTMENT CLASSES - Inggrid Brita Mathew (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
English department students at Padang State University are both multilingual and heading into a multilingual world and workplaces. Prudent use can be made of their previous and on-going experience of language acquisition when teaching English. Four strategies are described. For grammar/speaking classes brief comparative analysis of  a problematic English sentence structure with other languages can be made.. For pronunciation classes, sounds where errors are frequently found can be taught by looking for any allophonic equivalent from another language available in the classroom. For vocabulary and translation classes the mis-match between lexical concepts in languages the students are familiar with can be exploited to help students deal with that concept in English. Student experience of multiple language-based identities can be used in the cross-cultural communication classroom can provide a stepping stone to interacting across different languages and cultures.